Humic acids increase the maize seedlings exudation yield - Luciano P. Canellas; Fábio L. Olivares; Natália O. A. Canellas; Pierluigi Mazzei; Alessandro Piccolo (Chemical and Biological Technologies in Agriculture, 2019)
Abstract Background The role of humic acids in root crosstalk signaling has been demonstrated, including modification of soil properties, plant physiology, and regulation of microbial community structure. The exudation underpins nearly all major changes that occur in the rhizosphere playing active role in the regulation of ecosystem functioning. Modifications in exudation yield or its chemical composition are a possibility for rhizosphere manipulation with beneficial outcomes for plant growth and development. We reported here the main changes occurred in exudation profile of maize seedlings induced by humic acids isolated from vermicompost. Results The yields of exudate were enhanced by exogenous humic acids, whereas its profile remained unaltered in comparison with non-treated plants, as shown by 1H NMR spectra. Conversely, the gas chromatography coupled to time-of-flight high resolution mass spectrometry revealed a change in the molecular distribution of exudate and, in particular, an increase in concentration of compounds related to phenyl propanoids pathway (hydroxycinnamic, cinnamic, and ferulic acid), TCA cycle (malic, succinic, citric, and aconitic acids), amino acids (homoserine, citrulline, aspartic acid), lipids (linoleic acid, caprylic acid, pimelic acid), and carbohydrates (xylolactone, tagatose, sophorose, maltose, glucose-6-phosphate, and erythritol). Conclusion The increase on exudation yield induced by humic acids enhanced the release of a plethora of chemical compounds to root interface. This supports the concept that humic substances influence microbial population size and microbial community structure as well as confirms their role at root chemical interface.